UPAYA BADAN PELAYANAN PERIJINAN TERPADU DAN SATPOL PP TERHADAP PENERTIBAN PEMONDOKAN TIDAK MEMILIKI IJIN - Septa Kurnia Wahyudi (Jurnal Cakrawala Hukum, 2017)
The issues raised based on the efforts made by the Integrated Licensing Service and Satpol PP Malang city in controlling the lodging business that has no permit in Malang and its obstacles. The approach method used is sociological juridical, using descriptive analysis. The results of the research can be seen that there are efforts that preventif, by patrolling and supervising tramtibum and enforcement of local regulations and decisions of the mayor and repressive efforts, among others by calling, examination, investigation, and Pengkasan news event examination (BAP) for filed in the Tipiring Session. Obstacles in the effort to curb this lodgement business there are 2 namely the internal and external barriers Satpol PP, external obstacles such as Lack of public understanding of the basic tasks Satpol PP, Ignorance of society against the applicable legislation. The bravery of local offenders violates officers. As for internal barriers such as the quality of existing employees is still lacking, the lack of educational background by personnel Satpol PP so as not been able to understand the duties and functions of the institution principal, and frequent personnel mutations so that less maximumcoaching.DOI: https://doi.org/10.26905/idjch.v8i2.2115